Investigating the effect of premarital education based on the SYMBIS model on communication skills and conflict resolution skills of fiancés - Majidi, Elham; Asgari Dehaghani , Hengameh; Dehghani, Marziyeh; Samadi, Mohammad (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The purpose of this study was to investigate the effect of premarital education based on the SYMBIS model on communication skills and conflict resolution skills of fiancés. Method: In terms of the purpose, the current research was of an applied type, and in terms of the research design and method, it was a quasi-experimental design with a pre-test and post-test design with an experimental group and a control group and a three-month follow-up period. Based on this, the statistical population of the research included all the fiancés who referred to the counseling centers of the 7th district of Tehran to receive pre-marital counseling in the first half of 2011. Therefore, 40 people (20 couples) were selected from among these people and were randomly assigned to an experimental group (20 people) and a control group (20 people). Then, premarital education based on the SYMBIS model prepared by Les and Leslie Perot (2006) was implemented on the experimental group. Also, in order to collect data, the research tools included the conflict resolution questionnaire (CRQ) and the communication skills questionnaire of Christensen and Salluvay (1984). In the descriptive part, frequency distribution tables were used, and in the inferential part of data analysis, mixed variance analysis with repeated measurements and Bonferroni's post hoc test and SPSS software version 26 were used. Results: The F value and the significance level of the obtained value were calculated in the variable of communication skills (F = 7.83 and P = 0.004) and conflict resolution skills (F = 6.91 and P = 0.006). Therefore, it can be concluded that the independent variable i.e. premarital education based on the SYMBIS model has significantly changed the dependent variables i.e. communication skills and conflict resolution skills. This means that the changes made in the dependent variables were caused by the membership in the experimental group or the independent variable (premarital education based on the SYMBIS model). Conclusion: Based on the findings, it can be concluded that premarital education based on the SYMBIS model is effective on the communication skills and conflict resolution skills of the fiancés. Therefore, this model can be used in premarital counseling.